Rose’s Turn: How Women in Positions of Political Leadership Handle Terrorism on the Homefront - Engber, Hannah (Journal of Management Policy and Practice, 2020)
From Elizabeth II to Hillary Clinton, women in political leadership roles have been judged far more mercilessly for their decisions, especially those requiring force. Over the decades, some argue that their female bodies are too emotional to handle issues like terrorism appropriately. Others argue that it is because of their maternal instincts and protectiveness make them entirely unfit to handle tough decisions. By looking at figures like Margaret Thatcher and Golda Meir and through analysis of their counterterrorism policies in their nations, one can begin to distinguish the difference, if any, between women and men as public leaders.